2017
DOI: 10.2147/ott.s93629
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholangiocarcinoma: current perspectives

Abstract: Intrahepatic cholangiocarcinoma (ICC) is the second most common malignancy arising from the liver. ICC makes up about 10% of all cholangiocarcinomas. It arises from the peripheral bile ducts within the liver parenchyma, proximal to the secondary biliary radicals. Histologically, the majority of ICCs are adenocarcinomas. Only a minority of patients (15%) present with resectable disease, with a median survival of less than 3 years. Multidisciplinary management of ICC is complicated by large differences in diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
114
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 128 publications
0
114
0
3
Order By: Relevance
“…In contrast to previous studies, which have included only two or three factors in the prediction of OS, our calculator assigned weights to each of the variables included in the multivariable model. Indeed, previous multi‐institutional and registry analyses have demonstrated that except for tumor size and number, other factors such as CA19‐9 levels, margin, and lymph node status as well as major and microscopic vascular invasion are important determinants of long‐term outcomes, and, thus, should be taken into account when predicting the OS of patients with ICC . As such, our calculator could provide a more accurate prediction of long‐term outcomes for patients undergoing surgery for ICC.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies, which have included only two or three factors in the prediction of OS, our calculator assigned weights to each of the variables included in the multivariable model. Indeed, previous multi‐institutional and registry analyses have demonstrated that except for tumor size and number, other factors such as CA19‐9 levels, margin, and lymph node status as well as major and microscopic vascular invasion are important determinants of long‐term outcomes, and, thus, should be taken into account when predicting the OS of patients with ICC . As such, our calculator could provide a more accurate prediction of long‐term outcomes for patients undergoing surgery for ICC.…”
Section: Discussionmentioning
confidence: 99%
“…ICC carries a dismal prognosis, with 3‐ and 5‐year survival rates of 30% and 18% . Surgical resection is recommended whenever possible; however, as few as 15% of patients may present with inoperable disease . For those who are not surgical candidates, systemic chemotherapy is the standard of treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Intrahepatic cholangiocarcinoma (ICC) occurs in approximately 1‐2 per 100 000 persons, making it the second most common primary hepatic malignancy . Although ICC mostly develops as a well‐differentiated carcinoma, only a minority (15%) of patients presents with resectable disease at the time of diagnosis . Complete surgical resection remains the only option for cure.…”
Section: Introductionmentioning
confidence: 99%